2007
DOI: 10.1179/107735207800244910
|View full text |Cite
|
Sign up to set email alerts
|

A Successful Workplace Program for Voluntary Counseling and Testing and Treatment of HIV/AIDS at Heineken, Rwanda

Abstract: Heineken Breweries launched a workplace HIV/AIDS program at its Rwanda subsidiary in September 2001. By January 25, 2005, 736/2,595 eligible individuals had reported for counseling and HIV testing: 380/521 employees (72.9%), 254/412 spouses (61.7%), 99/1,517 children (6.5%), and 3/145 retired (2.0%). As a result, 109 HIV+ individuals were identified: 62 employees, 34 spouses, 12 children, and 1 retired. In September 2003 an anonymous HIV seroprevalence survey was performed with participation rates of 69.4% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 4 publications
0
19
0
9
Order By: Relevance
“…61 studies reported uptake of different community-based testing approaches among 713,632 participants: seven studies evaluated index testing among 12,052 participants [29],[30],[41][46], three evaluated self-testing among 1,839 participants [47][49], 14 evaluated mobile HTC among 79,475 participants [26],[28],[50][59], 28 evaluated door-to-door testing among 555,267 participants [24],[25],[28],[30],[60][81], six evaluated workplace HTC among 62,406 participants [22],[82][86], and three evaluated school-based HTC among 2,593 participants [87][89] (Figure 2). The percentage of participants accepting HTC was 88.2% for index testing (95% confidence interval [CI] 80.5%–95.9%; I 2 99.7%, 95% CI 99.7%–99.8%; Figure 3), 87.1% for self-testing (95% CI 85.1%–89.0%; I 2 28.8%, 95% CI 0%–92.6%; Figure 4), 86.8% for mobile HTC (95% CI 85.6%–88.1%; I 2 99.9%, 95% CI 99.9%–99.9%; Figure 5), 80.0% for door-to-door HTC (95% CI 76.9%–83.1%; I 2 99.9%, 95% CI 99.9%–99.9%; Figure 6), 67.4% for workplace HTC (95% CI 32.8%–100.0%; I 2 100%, 100.0%–100.0%; Figure 7), and 62.1% for school-based HTC (95% CI 39.6%–84.5%; I 2 99.0%, 95% CI 98.5%–99.4%; Figure 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 studies reported uptake of different community-based testing approaches among 713,632 participants: seven studies evaluated index testing among 12,052 participants [29],[30],[41][46], three evaluated self-testing among 1,839 participants [47][49], 14 evaluated mobile HTC among 79,475 participants [26],[28],[50][59], 28 evaluated door-to-door testing among 555,267 participants [24],[25],[28],[30],[60][81], six evaluated workplace HTC among 62,406 participants [22],[82][86], and three evaluated school-based HTC among 2,593 participants [87][89] (Figure 2). The percentage of participants accepting HTC was 88.2% for index testing (95% confidence interval [CI] 80.5%–95.9%; I 2 99.7%, 95% CI 99.7%–99.8%; Figure 3), 87.1% for self-testing (95% CI 85.1%–89.0%; I 2 28.8%, 95% CI 0%–92.6%; Figure 4), 86.8% for mobile HTC (95% CI 85.6%–88.1%; I 2 99.9%, 95% CI 99.9%–99.9%; Figure 5), 80.0% for door-to-door HTC (95% CI 76.9%–83.1%; I 2 99.9%, 95% CI 99.9%–99.9%; Figure 6), 67.4% for workplace HTC (95% CI 32.8%–100.0%; I 2 100%, 100.0%–100.0%; Figure 7), and 62.1% for school-based HTC (95% CI 39.6%–84.5%; I 2 99.0%, 95% CI 98.5%–99.4%; Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…18 studies reported the CD4 counts of 8,993 participants found to be HIV-positive using point-of-care or standard lab diagnostics [29],[30],[51],[55],[56],[60],[61],[74],[76],[82],[110],[121],[124][127]. 56.7% (95% CI 49.6%–63.9%; I 2 97.6%, 95% CI 97.0%–98.1%; Figure 14) of participants testing positive had CD4 counts above 350 cells/µl.…”
Section: Resultsmentioning
confidence: 99%
“…The preference to access HIV care outside their workplace is contrary to the recommendation to provide such care at the workplace, which has been found to be cost-effective [36], [37]. Offering HCWs a package of services not only for HIV and TB but also for infectious and non-communicable diseases may be the way to go.…”
Section: Discussionmentioning
confidence: 98%
“…Men – who access the health system less frequently than women – are tested in higher numbers when HIV testing is offered at work sites as compared to HIV testing clinics (e.g. 51.1% vs. 19.2%) [7, 8]. And, although the evidence is limited, provider-initiated testing and counselling of children in key health service entry points have shown an average yield of 16.6%, with paediatric inpatient units showing 22.5% [9].…”
Section: Introductionmentioning
confidence: 99%